Criticality Analysis of HTR-10 using an Open Source Monte Carlo code OpenMC - Ikhsan Mahfudin; Topan Setiadipura (Pusat Kajian Sistem Energi Nuklir, Badan Tenaga Nuklir Nasional, 2020)
As one of advance nuclear reactor design, capability to model and analyze the pebble bed reactor is important. Availability and capability of an accurate open source and open access software for pebble bed reactor analysis is strategic. It can broaden the involvement of more student and researcher which finally may improve the research and development in this field. Current study aim to develop the pebble bed core model and perform a criticality study of HTR-10 core design. This study exploit the capability of openMC software to model a double heterogenety geometry using a TRISO Pack Model Building based on random sequential packing and closed random packing. Physical parametric surveys of the developed model show an expected results in which the model able to reflect the negative reactivity feedback of HTR-10 design. The critical height of HTR-10 model with helium from current model, VSOP, and MCNP are 125.881 cm, 125.804 cm, 126.116 cm, respectively. A code-to-code criticality analysis comparison of current model with VSOP and MCNP code reported by INET shows a good comparison and suggest that current method can be used for further pebble bed analysis.